The Functionalisation of Terpenes for Sustainable Polymerisations Towards Biomedical Applications - O'Brien, Dara (2021)
This thesis details a variety of methods in which monoterpenes can be employed in different stages of sustainable polymerisation mechanisms, with a view to using the polymeric materials in biomaterials applications such as anti-microbial formulations.